Wound Irrigation Using Wet Gauze May Reduce Surgical Site Infection Following Laparoscopic Appendectomy - Al-Sawat, Abdullah; Mun, Ji Yeon; Yoon, Sung Hoon; Lee, Chul Seung (Frontiers in Surgery, 2022)
Purpose: This study aimed to compare the perioperative outcomes of wet gauze and conventional irrigation after laparoscopic appendectomy to determine whether wet gauze irrigation can help reduce surgical site infection (SSI). Methods: A total of 308 patients undergoing laparoscopic appendectomy were included in this study between December 2018 and May 2020. Of these, 132 (42.9%) received gauze irrigation (group 1), and 176 patients (57.1%) received conventional irrigation (group 2). Preoperative outcomes and complications, including SSI, were compared after propensity score matching (PSM) to adjust for baseline differences and selection bias. Results: After 1:1 PSM, 92 well-matched patients in each group were evaluated. Regarding perioperative outcomes between groups 1 and 2, the rate of severe complications (Clavien-Dindo Classification grades III, IV, and V), operative time, and readmission rate did not differ between the groups. Superficial/deep SSIs were observed more frequently in group 2 (8/92 cases) than in group 1 (1/92 cases; p=0.017). The organ/space SSIs rate was not significantly different between the two groups (1/92 group 1 and 0/92 group 2, p=0.316). However, postoperative hospital stay was significantly longer in group 2 (2.8±1.3 days) than in group 1 (1.6±1.2 days; p<0.001). In the univariate analyses, wound irrigation using wet gauze was an independent protective factor for superficial or deep SSI (p=0.044). Conclusions: Wound irrigation using wet gauze after fascia closure has a significant beneficial effect on reducing postoperative superficial/deep SSI following laparoscopic appendectomy.